2018
DOI: 10.3389/fevo.2018.00018
|View full text |Cite
|
Sign up to set email alerts
|

The Strength and Drivers of Bird-Mediated Selection on Fruit Crop Size: A Meta-Analysis

Abstract: In seed-dispersal mutualisms, the number of fruit a plant displays is a key trait, as it acts as a signal for seed dispersers that entails fruit removal and exportation of reproductive units (fruit crop size hypothesis). Although this hypothesis has gained general acceptance, forces driving the shape and strength of natural selection exerted by birds on fruit crop size remains an unresolved matter. Here, we propose that ecological filters promoting high functional equivalence of interacting partners (similar f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 128 publications
2
22
1
Order By: Relevance
“…Our results revealed that frugivores respond to crop sizes of fruiting plants, by visiting more frequently those plants bearing more fruits. These results are in line with previous studies that have also found a positive relationship between frugivore visitation and plant resource availability [see 69 and references therein]. Interestingly, the positive relationship between crop size and frugivore visitation was mostly driven by two functional groups of frugivores (i.e.…”
Section: Discussionsupporting
confidence: 92%
“…Our results revealed that frugivores respond to crop sizes of fruiting plants, by visiting more frequently those plants bearing more fruits. These results are in line with previous studies that have also found a positive relationship between frugivore visitation and plant resource availability [see 69 and references therein]. Interestingly, the positive relationship between crop size and frugivore visitation was mostly driven by two functional groups of frugivores (i.e.…”
Section: Discussionsupporting
confidence: 92%
“…With respect to the proportion of seeds dispersed, results to date show no consistent relationship (Table 2). These patterns suggesting a general increase in the number but not the proportion of seeds dispersed with increasing crop size are supported by a meta-analysis that found positive bird-mediated selection on fruit crop sizes as measured by both visitation rate and the quantity of seeds dispersed, but no selection on the proportion of seeds dispersed (Palacio and Ordano 2018).…”
Section: Intrinsic Variation: Plant Traitsmentioning
confidence: 82%
“…We developed three competing a priori hypotheses based on our understanding of the relationships between plants, fruit and seed traits, seed removal, fruit infestation and parasitoids ( Figure 2). The initial full SEM hypothesized that both birds (Palacio et al, 2014;Palacio & Ordano, 2018;Siepielski & Benkman, 2007a) and ants (Alcántara et al, 2007;Manzaneda, Rey, & Alcántara, 2009) act as agents of selection on fruit and seed traits, so we connected the two fruit traits (fruit crop size and mean sugar concentration) and mean seed size to bird fruit removal, and mean sugar concentration and mean seed size to ant seed removal ( Figure 2). The number of fruits produced is often a function of plant size and neighbour density (Minor & Kobe, 2019), so we included a path connecting tree height, DBH and the distance to the nearest neighbour to fruit crop size, as well as a correlation between tree height and DBH.…”
Section: Discussionmentioning
confidence: 99%
“…Given that each fruit encloses only one seed, fruit removal equals seed removal. Fruit removal was used as a surrogate for tree fitness (Jordano, 1995; Palacio & Ordano, 2018; Siepielski & Benkman, 2007a; Sobral, Guitián, Guitián, & Larrinaga, 2013) in the context of selection by bird and ants, under the assumption that trees with a higher number of seeds dispersed would have greater potential for dispersal and germination of their seeds (Primack & Kang, 1989; Siepielski & Benkman, 2007a, 2008a; see Section 4). Although the proportion of fruits removed may be a better surrogate of fitness for plants whose reproductive output is size‐dependent (Jordano, 1995; Siepielski & Benkman, 2007b; but see Palacio & Ordano, 2018), we used the number of fruits removed as a fitness component because tree size and fruit crop size were included as covariates in the statistical models (see below).…”
Section: Methodsmentioning
confidence: 99%